Pengaruh Keahlian Kerja, dan Kemampuan Kerja Terhadap Kinerja Karyawan Pada PDAM Kabupaten Luwu - Riady, Ahmad; Sampetan, Suparni; Sukri, Sukri (JURNAL ILMIAH EDUNOMIKA, 2024)
The purpose of this research is to determine the effect of work skills on employee performance, the effect of work skills on employee performance, as well as the effect of work skills and work abilities on employee performance at PDAM Luwu Regency. This research is a type of descriptive quantitative research. The population in this study was all employees at PDAM Luwu Regency with a total of 70 people. Sampling used Nonprobability Sampling with saturated sampling techniques. The number of samples used in this research was 70 people. The types and sources of data used in this research are primary data and secondary data. The work skills variable (X1) is stated to have no effect and is not significant on employee performance (Y). while the work ability variable (X2) is stated to have a significant and influential effect on employee performance (Y). In the Simultaneous Test, Work Skills and Work Ability have a joint (simultaneous) and significant effect on Employee Performance at PDAM Luwu Regency. Training is needed for the skills of each employee, as well as increasing the work ability of employees at PDAM Luwu Regency.